2015
DOI: 10.1055/s-0035-1548929
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Nitric Oxide Synthases and Na+/K+-ATPase in the Rat Model of Polycystic Ovary Syndrome Induced by Dihydrotestosterone

Abstract: Nitric oxide synthases (NOSs) and Na(+)/K(+)-ATPase are enzymes essential for regular functioning of the heart. Since both enzymes are under insulin and androgen regulation and since insulin action and androgen level were disturbed in polycystic ovary syndrome (PCOS), we hypothesized that cardiac nitric oxide (NO) production and sodium/potassium transport would be deteriorated in PCOS. To test our hypothesis we introduced animal model of PCOS based on dihydrotestosterone (DHT) treatment of female Wistar rats a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Levels of NO in FF were found to affect the development and fertilization of oocytes [43]. Levels of iNOS protein in the hearts of dihydroxytestosterone-treated rats were significantly elevated [44]. In this study, we observed higher lipid peroxidation in the FF of PCOS patients.…”
Section: Discussionsupporting
confidence: 55%
“…Levels of NO in FF were found to affect the development and fertilization of oocytes [43]. Levels of iNOS protein in the hearts of dihydroxytestosterone-treated rats were significantly elevated [44]. In this study, we observed higher lipid peroxidation in the FF of PCOS patients.…”
Section: Discussionsupporting
confidence: 55%
“…In this sense, the androgen-induced PCOS model could be appropriate to examine both ovarian morphology and metabolic aspects of PCOS. Regarding the PCOS rat model and CV features, it is known that rats with PCOS showed increased sympathetic activity and HT [12], as well as impaired NO synthase and Na/K-ATP-ase activity in the heart tissue [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, prooxidative effects of testosterone and its derivatives on CV [17], endocrine [18], and behavioral [19,20] properties were proven in our previous papers, dealing with the administration of supraphysiological doses in male rats. Investigations with similar protocols in female rodents have not been represented in literature so far, except androgen administration to female rats to mimic PCOS characteristics [13]. The data concerning PCOS models demonstrated increased oxidative stress with impairment of antioxidant protection in different tissues, such as liver, muscle, and periovarial fat tissue [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, these are the vital enzyme acting as an antitoxin against anion of super oxide16. Similarly, in a few studies, it was also found that elevation of oxidative pressure was observed even in obese females with PCOs 17 . Literature in the past suggests that the concentration of extracellular SOD increases after a vascular injury that significantly leads to vascular endothelium tissue damage 18 .…”
Section: Discussionmentioning
confidence: 69%